2015
DOI: 10.1164/rccm.201502-0235le
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eosinophils: A Biomarker of Response to Extrafine Beclomethasone/Formoterol in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a heterogeneous condition (1). The identification of COPD phenotypes may allow stratified treatment approaches that modulate discrete disease mechanisms. Peripheral blood eosinophilia is both a common and repeatable finding in COPD (2). In addition, the presence of a blood/sputum eosinophilia is associated with a significant proportion of COPD exacerbations (3, 4) and a favorable response to systemic steroids (5). However, the role of blood eosinophils in stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
289
7
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(323 citation statements)
references
References 7 publications
10
289
7
17
Order By: Relevance
“…4). A series of further post-hoc analyses in other data sets confirmed this observation 41,42 although there was no particular benefit in this subgroup when ICS/LABA was compared to a LABA/ long-acting muscarinic antagonist (LAMA) combination 43 . Data from the large Withdrawal of Inhaled Steroids during Optimized Bronchodilator Management (WIS-DOM) trial showed that ICS could be safely stopped in patients with severe COPD and an exacerbation history provided they continued with LABA and LAMA treatment 44 .…”
Section: Barcelona Respiratory Networkmentioning
confidence: 89%
“…4). A series of further post-hoc analyses in other data sets confirmed this observation 41,42 although there was no particular benefit in this subgroup when ICS/LABA was compared to a LABA/ long-acting muscarinic antagonist (LAMA) combination 43 . Data from the large Withdrawal of Inhaled Steroids during Optimized Bronchodilator Management (WIS-DOM) trial showed that ICS could be safely stopped in patients with severe COPD and an exacerbation history provided they continued with LABA and LAMA treatment 44 .…”
Section: Barcelona Respiratory Networkmentioning
confidence: 89%
“…Most of the studies [155][156][157] except one 158 have demonstrated that high blood eosinophils could be valuable to predict an increase response in terms of reduction of exacerbation rate when treated with combination ICS/LABA. However, all these studies were secondary analyses or post hoc subgroup analyses.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Furthermore, there is still uncertainty about the exact cut-off level of blood eosinophils having potential therapeutic value. Some studies 155,157 have shown a better response in patients with blood eosinophils 2% while in other studies 159 a cut-off of 4% or eosinophil count >300 cells/mL has been suggested. Data suggests that in COPD, blood eosinophil levels >340 cells/mL is associated with a 1.76 fold increased risk of severe exacerbations 160 ; however using the 2% cut-off in this study did not predict increased risk of exacerbations.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…В последнее время при решении вопроса о выборе иГКС содержащей терапии у больных ХОБЛ обсуж дается значение такого биомаркера, как эозинофи лия периферической крови [26][27][28]. В исследовании WISDOM, в котором изучалось влияние отмены иГКС на частоту среднетяжелых / тяжелых обостре ний ХОБЛ у больных, получавших тройную терапию, показано, что частота обострений после отмены иГКС не нарастала, хотя в группе отмены иГКС отме чалось достоверное снижение ОФВ1 и ухудшение ка чества жизни пациентов в конце исследования.…”
unclassified